2020
DOI: 10.1186/s12933-020-01007-6
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference is associated with major adverse cardiovascular events in male but not female patients with type-2 diabetes mellitus

Abstract: Background: Although studies have shown that waist circumference (WC) is positively associated with an increased risk of cardiovascular diseases among the normal population, few studies have investigated WC in patients with type-2 diabetes mellitus (T2DM). Methods: This was a post hoc analysis of the Action to Control Cardiovascular Risk in Diabetes (ACCORD) study. The Cox proportional hazards models was used to investigate the relationship between WC and major adverse cardiovascular events (MACEs) in T2DM pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…We also noted that combining WC and HGS/BW, a potential proxy fat: muscle index, had a summative effect on the risk of having a higher MetS score. Our cross-sectional analysis showed a stronger association between a higher MetS score and WC than BMI, confirming previous studies showing that in Latin-American and Chinese population, WC is a stronger predictor of major cardiovascular events such as myocardial infarction or stroke than BMI, particularly in men [8,21]. Similarly, in diabetic Chinese adults, high visceral fat measured by a visceral adiposity index and WC were associated with a higher prevalence of diabetic kidney disease and CVD compared to BMI [22].…”
Section: Combining Adiposity and Muscle Strength Measurements Increases The Prediction Of Metabolic Alterationssupporting
confidence: 91%
“…We also noted that combining WC and HGS/BW, a potential proxy fat: muscle index, had a summative effect on the risk of having a higher MetS score. Our cross-sectional analysis showed a stronger association between a higher MetS score and WC than BMI, confirming previous studies showing that in Latin-American and Chinese population, WC is a stronger predictor of major cardiovascular events such as myocardial infarction or stroke than BMI, particularly in men [8,21]. Similarly, in diabetic Chinese adults, high visceral fat measured by a visceral adiposity index and WC were associated with a higher prevalence of diabetic kidney disease and CVD compared to BMI [22].…”
Section: Combining Adiposity and Muscle Strength Measurements Increases The Prediction Of Metabolic Alterationssupporting
confidence: 91%
“…The result of a cross-sectional study has shown that obesity and type 2 diabetes have an additive effect on left ventricular remodeling in normotensive patients ( 28 ). A recent study of patients with type-2 DM showed that compared with those in the first quartile of WC, male patients in the fourth quartile of WC (WC ≥ 126) had an HR of 1.24 (95% CI: 1.05–1.46) for major adverse cardiovascular events (MACEs); female patients in the fourth quartile of WC (WC ≥ 122 cm) had an HR of 1.22 (95% CI: 0.96–1.56) for MACEs ( 29 ). Our results suggested that patients with higher levels of WC coexisted with diabetes had the worst outcome, the association is still significant after adjustment of other clinical confounders.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that people with higher WC levels have 5–7 times higher chances of having T2DM. 45 …”
Section: Discussionmentioning
confidence: 99%